Nitrogen fertilization improves the agro-morphological and yield attributes of Sinapis alba L. - Haq, Ehsan Ul; Hassan, Fayyaz Ul; Zhou, Fanrui; Gong, Xiaomin; Manaf, Abdul; Shabbir, Ghulam; Karim, Muhammad Fazal; King, Patricia Jie Hung; Adil, Muhammad Faheem; Shamsi, Imran Haider (Multidisciplinary Digital Publishing Institute, 2023)
Oilseed crops play a vital role in the economy of Pakistan, yet the production of oilseeds is far less than the demand for them. White mustard (Sinapis alba L.) is an emerging crop, that belongs to the Brassicaceae family. It is considered to be an alternative to all other oilseed crops for dry temperate climates. White mustard develops rapidly, and has a large canopy and deep rooting system; hence, it can draw up nutrients from deeper layers. This study aimed to evaluate the influence of nitrogen on S. alba agro-morphological attributes and enhance nutrient use efficiencies. During the Rabi seasons of 2019-20 and 2020-21, an experiment was conducted at the University Research Farm, Chakwal Road, Rawalpindi. The study included seven treatments, i.e., T1-Control, T2-20, T3-40, T4-60, T5-80, T6-100, and T7-120 kg·ha−1. Each treatment was replicated three times, and the study utilized a randomized complete block design (RCBD). The results revealed that nitrogen at 100 kg·ha−1 was the optimal concentration and significantly increased the agro-morphological parameters, i.e., plant height (47.01), primary branches (41.36), secondary branches (45.33), 1000 seed weight (54.35), siliques/plant (41.57), seeds/silique (52.30) biological yield (68.38), seed yield (54.90), harvest index (11), and oil yield (38.84), as compared to the control. Moreover, protein contents and oil contents were significantly increased (5.15 and 6, respectively), as compared to the control, while glucosinolate content was decreased (4.36). Similarly, maximum agronomic efficiency (AE), apparent recovery efficiency (ARE) (53), physiological efficiency (PE), and nutrient use efficiency (NUE) were also improved, as compared to the control. Hence, N application at a concentration of 100 kg·ha−1 can be recommended for S. alba under the present cropping system of Pothwar.